2022
DOI: 10.3390/v15010063
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus (HEV) Synopsis: General Aspects and Focus on Bangladesh

Abstract: HEV is the most common cause of acute hepatitis globally. This review summarizes the latest knowledge on the epidemiology, clinical characteristics, testing, and treatment of HEV infection. We also focused on Bangladesh to highlight the distinct challenges and the possible remedies. In low-income settings, the virus is mainly transmitted between people by fecal contamination of drinking water causing large outbreaks, and sporadic cases. The disease is usually mild and self-limiting acute hepatitis. Still, preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…HEV-gt3 and 4 infections are the most successful zoonotic viral diseases in human history and cause zoonotic food-borne autochthonous infections in industrialized countries. With the availability and application of HEV diagnostics, the existence of hepatitis E in several other forms has been established including transfusion-transmitted infections, inducing screening programs by several countries, a large pool of HEV-gt3 chronic liver disease in solid organ transplant, HIV, and hematopoietic neoplasm patients, masquerading as drug-induced liver injury, and a series of syndromes caused by extrahepatic manifestations of HEV [136,146,147]. The development of accurate diagnostic assays for the detection of HEV infection remains challenging and many outstanding issues remain (Table 3) [150].…”
Section: Hepatitis Ementioning
confidence: 99%
See 1 more Smart Citation
“…HEV-gt3 and 4 infections are the most successful zoonotic viral diseases in human history and cause zoonotic food-borne autochthonous infections in industrialized countries. With the availability and application of HEV diagnostics, the existence of hepatitis E in several other forms has been established including transfusion-transmitted infections, inducing screening programs by several countries, a large pool of HEV-gt3 chronic liver disease in solid organ transplant, HIV, and hematopoietic neoplasm patients, masquerading as drug-induced liver injury, and a series of syndromes caused by extrahepatic manifestations of HEV [136,146,147]. The development of accurate diagnostic assays for the detection of HEV infection remains challenging and many outstanding issues remain (Table 3) [150].…”
Section: Hepatitis Ementioning
confidence: 99%
“…HEV in these regions is the most common cause of acute sporadic hepatitis, acute liver failure, and acute-on-chronic liver failure. There is an enormous load of hepatitis E in pregnancy and fetal/neonatal HEV infections [ 146 , 147 ]. Of late, there are declining trends in these figures due to improvements in sanitation in India.…”
Section: Hepatitis Ementioning
confidence: 99%
“…HEV infection during pregnancy causes various adverse maternal and neonatal outcomes in low-income and middle-income countries where sanitation is poor and HEV infection frequently leads to outbreaks [ 8 , 10 , 12 , 13 , 14 , 15 , 16 ]. In this study, no severe disease or maternal mortality was observed in HEV-infected pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HEV infection in pregnant women can lead to adverse fetal outcomes, including preterm delivery, low birth weight, spontaneous abortions, and stillbirths [ 8 , 12 ]. These adverse outcomes of HEV infections in pregnant women and their fetuses or neonates have been well documented in relation to HEV-1 and HEV-2 in low-income and middle-income countries with poor sanitation, including Bangladesh [ 13 ], India [ 8 , 12 , 14 ], Chad [ 15 ], Niger [ 10 ], and Sudan [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Every year, 20 million new HEV infections, with 3.3 million acute clinical cases and over than 44.000 related deaths are reported worldwide (9). Hepatitis E virus-1 and HEV-2 are epidemic and endemic in developing countries in Asia and Africa, while HEV-3 and HEV-4 are sporadic in developed countries in Europe, North America and Japan (10)(11)(12)(13), causing a variety of hepatic and extrahepatic manifestations (14). Hepatitis E virus-3, 4 and 7 infections are zoonotic (15) transmitted between animals and humans by consumption of raw or undercooked meat (HEV3 and 4) and milk (HEV-7) or contact with infected animals (16).…”
Section: Introductionmentioning
confidence: 99%